Development of Islamic economics and practices in Indonesia (2013-2023): opportunities and challenges - Nursaid, Nursaid; Smith, Zain; Dhakal, Amrit (Revenue Journal: Management and Entrepreneurship, 2023)
Despite the immense growth potential, implementing Islamic economics in Indonesia encounters substantial hindrances. An issue arises from the Muslim populace's constrained knowledge and comprehension of Islamic economics. This is evident from the customer base disparity between Sharia-compliant and conventional banks. The progress of the Islamic economy is evident in the gradual expansion of Sharia banking annually, albeit sluggishly. In the future, implementing Islamic economics will encounter obstacles, including a scarcity of proficient experts in Islamic economics, insufficient public knowledge of the Islamic economic system, and the nonexistence of an Islamic economics syllabus across different educational levels. These issues contribute to the public's unfavourable perceptions of the Islamic economic system. This study analyses the obstacles and potential advantages of integrating Islamic economic principles into Indonesia's economic development while considering the existing framework of conventional economic growth. The field of Islamic economics has achieved significant progress. However, there are still barriers that could hinder its ability to achieve its objectives. The data utilized for analysis consists of a blend of primary and secondary sources. Data collection primarily involved disseminating questionnaires, encompassing both closed and open-ended inquiries, to a cohort of 26 individuals. The secondary data for this study was collected from many sources, such as academic journals, official websites, and related literature published between 2013 and 2023. The article's findings indicate a favourable trajectory for advancing Islamic economics in Indonesia. The existing legislation explicitly recognizes the participation of Sharia economic practitioners and respects the fact that Indonesia has a predominantly Muslim population. Nevertheless, the study will thoroughly examine the various obstacles to advancing Islamic economics in Indonesia.